The Effects of Resisted Post-Activation Sprint Performance Enhancement in Elite Female Sprinters - Matusiński, Aleksander; Pietraszewski, Przemysław; Krzysztofik, Michał; Gołaś, Artur (Frontiers in Physiology, 2021)
Considering the effectiveness of resisted sprint training, and the acute enhancement of sprinting performance through locomotor post-activation performance enhancement, the main objective of the research was to determine the acute effects of resisted activation with loads of 5, 10, and 15% body mass on sprint and flying start sprint performance in elite female sprinters using resisted drag technology system. Ten elite female sprinters (age: 23.2 ± 5.4 years, body mass: 54.2 ± 6.1 kg, height: 167.4 ± 7.3 cm, personal best for 100 m: 12.05 ± 0.56 s, and for 400 m: 53.17 ± 2.76 s) performed two unresisted 20 m sprints (from a crouched and flying start) before and after a single resisted sprint loaded with either 5, 10 or 15% body mass to verify the effectiveness of the activation stimulus. Compared with pre-activation, Friedman tests showed that peak velocity increased by 1.62.2% (ES=0.66), 2.31.5% (ES=1.33), and 0.21% (ES=0.09), as well as peak force by 2.82.1% (ES=0.49), 3.52.3% (ES=1), and 0.52.4% (ES=0.14), concomitant with a significant decreased in sprint time by -0.51.2% (ES=-0.07), -2.51.3% (ES=-0.64), -11.4% (ES=-0.36) for the 5%, 10% and 15% body mass post-activation, respectively (p<0.001; for all). Furthermore, the ANOVA showed that peak power increased by 2.92.3% (ES=0.61), 3.82.2% (ES=1.05), and 27.1% (ES=0.22) for the 5%, 10% and 15% body mass resisted-conditioning activity, respectively, with no difference between the 3 conditions (p=0.003 main effect time, no interaction). Moreover, compared with the 5% and 15% body mass trial (-1.52% (ES=-0.44), -0.80.8% (ES=-0.44; respectively), the ANOVA showed that flying start sprint time significantly decreased by -4.31.1% (ES=-1.25), (p<0.001, interaction effect) after a 10% body mass resisted-conditioning activity. The results of this study indicated that resisted sprints acutely enhance sprint performance, however their effectiveness depends on the applied load. A single resisted sprint using 10% body mass is effective at inducing a potentiating effect on subsequent 20m flying start sprint performance in elite female sprinters. Therefore, keeping in mind the optimal load, it is recommended to perform resisted sprints as a conditioning activation when seeking to acute enhance 20 m flying start sprint performance in these athletes.